Critical influence of reduced graphene oxide mediated binding of M (M = Mg, Mn) with Co ions, chemical stability and charge storability enhancements of spinal-type hierarchical MCo2O4 nanostructures - Krishnan, S.G. (Elsevier Ltd, 2017)
This paper reports that addition of reduced graphene oxide (rGO) in MgCo2O4 improves the binding of Mg with Co thereby minimizing magnesium dissolution in aqueous alkaline electrolytes and the resulting MgCo2O4/rGO electrodes offered impressive improvements in charge storage properties. An isostructural high performing material, MnCo2O4, is used as a benchmark material in this work. The Mg analogues stored >30 more charges than the Mn-analogues in the 3 M LiOH electrolyte despite the former's lower BET surface area; rGO modification further increased charge storage by?>60 than the unmodified analogues. Electrochemical measurements show that a larger surface fraction of the Mg analogue is electrochemically active, irrespective of whether or not rGO is present, which arise from, typically for MgCo2O4/rGO, lower internal resistance, lower Warburg impedance, and lower charge transfer resistance than the other electrodes. © 2017 Elsevier Ltd